2022
DOI: 10.7150/thno.72471
|View full text |Cite
|
Sign up to set email alerts
|

DDX56 transcriptionally activates MIST1 to facilitate tumorigenesis of HCC through PTEN-AKT signaling

Abstract: Rationale : Hepatocellular carcinoma (HCC) is a primary malignancy of the liver that is the leading cause of cancer-related mortality worldwide. However, genetic alterations and mechanisms underlying HCC development remain unclear. Methods: Tissue specimens were used to evaluate the expression of DEAD-Box 56 (DDX56) to determine its prognostic value. Colony formation, CCK8, and EdU-labelling assays were performed to assess the effects of DDX56 on HCC proliferation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the previous bioinformatics prediction, TBRG4 showed a strong correlation with DDX56. Studies have shown that DDX56 can inhibit the proliferation and migration of HCC cells through the PTEN/p-AKT signaling pathway [ 18 ]. We speculate that TBRG4 may participate in the AKT signaling pathway through DDX56.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous bioinformatics prediction, TBRG4 showed a strong correlation with DDX56. Studies have shown that DDX56 can inhibit the proliferation and migration of HCC cells through the PTEN/p-AKT signaling pathway [ 18 ]. We speculate that TBRG4 may participate in the AKT signaling pathway through DDX56.…”
Section: Resultsmentioning
confidence: 99%
“…DDX56 is a component of 65S ribosomal precursor particles that regulate various RNA metabolism processes, including transcription [ 26 ]. Research has shown that DDX56 interacts with MECOM to promote the growth of HCC cells through the PTEN/p-AKT signaling pathway [ 18 ]. Our study found that downregulating TBRG4 can reduce the expression of DDX56/p-AKT.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that Bmi-1 transcriptionally repressed the tumor suppressor phosphatase and tensin homolog (PTEN), thereby activating the phosphoinositide 3-kinase (PI3K)/AKT pathway, inducing the EMT and promoting the invasion and metastasis of NPC cells [23]. The suppression of PTEN has been shown to activate the PI3K/AKT/ glycogen synthase kinase 3β pathway in various kinds of cancer cells, thus greatly promoting their proliferation and stemness [71][72][73][74][75][76][77]. These data suggest that Bmi-1 may enhance the proliferation and stemness of NPC cells by inducing PTEN/PI3K/AKT signaling, although further investigation is needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…CircRHOBTB3 (circ_0007444) was reported to inhibit EOC progression by serving as a ceRNA to facilitate PTEN expression [ 110 , 111 ]. PTEN is a critical tumor suppressor in a variety of cancers, including EOC [ 202 , 203 , 204 , 205 ]. Wu et al [ 111 ] showed that circ_0007444 was markedly decreased in tumor samples, as compared with normal tissues.…”
Section: Circrnas As Potential Therapeutic Targetsmentioning
confidence: 99%